Antidotal effect of dihydroxyacetone against phosphine poisoning in mice. Issue 11 (27th August 2021) - Niknahad, Hossein; Heidari, Reza; Hashemi, Asieh; Jamshidzadeh, Akram; Rashedinia, Marzieh
Abstract: Phosphine (PH3 ) is widely used as an insecticide and rodenticide. On the contrary, many cases of PH3 poisoning have been reported worldwide. Unfortunately, there is no specific antidote against PH3 toxicity. Disruption of mitochondrial function and energy metabolism is a well‐known mechanism of PH3 cytotoxicity. Dihydroxyacetone (DHA) is an adenosine triphosphate supplying agent which significantly improves mitochondrial function. The current study was designed to evaluate DHA's effect on inhalational PH3 poisoning in an animal model. DHA was injected into BALB/c mice before and/or after the start of the PH3 inhalation. The cytochrome c oxidase activity was assessed in the animals' brain, heart, and liver exposed to PH3 (for 15, 30, and 60 min, with and without the antidote). The LC50 of PH3 was calculated to be 18.02 (15.42–20.55) ppm over 2 h of exposure. Pretreatment of DHA (1 or 2 g/kg) increased the LC50 of PH3 by about 1.6‐ or 3‐fold, respectively. Posttreatment with DHA (2 g/kg) increased the LC50 of PH3 by about 1.4‐fold. PH3 inhibited the activity of cytochrome c oxidase in the assessed organs. It was found that DHA treatment restored mitochondrial cytochrome c oxidase activity. These findings suggested that DHA could be an effective antidote for PH3 poisoning.